Complete Mitochondrial Genomes of the Cherskii's Sculpin Cottus czerskii and Siberian Taimen Hucho taimen Reveal GenBank Entry Errors: Incorrect Species Identification and Recombinant Mitochondrial Genome. (22nd August 2017) - Balakirev, Evgeniy S; Saveliev, Pavel A; Ayala, Francisco J
The complete mitochondrial (mt) genome is sequenced in 2 individuals of the Cherskii's sculpin Cottus czerskii . A surprisingly high level of sequence divergence (10.3%) has been detected between the 2 genomes of C czerskii studied here and the GenBank mt genome of C czerskii (KJ956027). At the same time, a surprisingly low level of divergence (1.4%) has been detected between the GenBank C czerskii (KJ956027) and the Amur sculpin Cottus szanaga (KX762049, KX762050). We argue that the observed discrepancies are due to incorrect taxonomic identification so that the GenBank accession number KJ956027 represents actually the mt genome of C szanaga erroneously identified as C czerskii . Our results are of consequence concerning the GenBank database quality, highlighting the potential negative consequences of entry errors, which once they are introduced tend to be propagated among databases and subsequent publications. We illustrate the premise with the data on recombinant mt genome of the Siberian taimen Hucho taimen (NCBI Reference Sequence Database NC_016426.1; GenBank accession number HQ897271.1), bearing 2 introgressed fragments (≈0.9 kb [kilobase]) from 2 lenok subspecies, Brachymystax lenok and Brachymystax lenok tsinlingensis, submitted to GenBank on June 12, 2011. Since the time of submission, the H taimen recombinant mt genome leading to incorrect phylogenetic inferences was propagated in multiple subsequent publications despite the fact that nonrecombinant H taimen genomes were also available (submitted to GenBank on August 2, 2014; KJ711549, KJ711550). Other examples of recombinant sequences persisting in GenBank are also considered. A GenBank Entry Error Depositary is urgently needed to monitor and avoid a progressive accumulation of wrong biological information.